HMG-COA Reductase Inhibition by Simvastatin Reduces Neointimal Inflammation in a Rat Model of Atherosclerosis - Sultana, Rezina; Rahman, Md Sayedur; Akhter, Nargis (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Inhibitors of HMG-CoA-reductase reduce cardiovascular mortality through the mechanisms yet elucidated. Most ischemic events are secondary to disruption of atherosclerotic plaques highly infiltrated by macrophages. Objectives: To study the effect of the 3-hydroxy-3-methyl-glutaryl coenzyme A (HMG-CoA)-reductase inhibitor simvastatin on the potential mechanisms involved in the recruitment of monocytic cells into the vessel wall. Methodology: This experimental study was carried out in the Laboratory of the Department of Pharmacology & Therapeutics, BSMMU, Shahbag, Dhaka, during the period from 1st July 2008 to 30th June 2009. Fifty healthy Long-Evans Norwegian male rats aged between 3-4 months and weighing between 180-200gm were randomly selected and divided into 3 groups (A, B & C). Control group A (n=10) were fed on standard rat diet for 8 weeks, Vehicle fed group B (n=10) were fed soybean oil at a dose of 1ml once daily for 8 weeks and 2% cholesterol fed group C (n=30) were fed a 2% cholesterol enriched diet (suspension of cholesterol powder in soybean oil) at a dose of 100mg/ml of 2ml once daily for 8 weeks. After 8 weeks 10 rats of each group were sacrificed and remaining 20 rats of group C were continued to the part II of the experiment and divided into two groups. Group-I (cholesterol fed control group, n=10) and Group-II (simvastatin treated group). Group-I fed 0.5ml of o.1% cholesterol enriched diet once daily to maintain atherosclerotic state & Group-II treated with 1ml of 60mg/ml simvastatin at a dose of 300mg/Kg/day along with 0.5ml of 0.1% cholesterol enriched diet. After 8 weeks all the rats of two group were sacrified. Blood collected from each rats for estimation of serum lipid profile by enzymatic methods and aorta was preserved for histopathological examination and Intima-media ratio was measured using Image-proplus software (Silva et al, 2000). Results: Simvastatin induced a significant reduction in serum lipids (p<0.001) and in atherosclerotic lesion size (p<0.001). Aortic macrophage infiltration was abolished by the treatment. Conclusions: In a rat atherosclerosis model, simvastatin diminished the neointimal inflammation and this could contribute to the stabilization of the atherosclerotic plaque. This may be an additional explanation for the reduction of acute ischemic events in patients treated with statins. DOI: http://dx.doi.org/10.3329/bjpp.v28i1-2.20073 Bangladesh J Physiol Pharmacol 2012; 28(1&2):5-9